2015
DOI: 10.1186/s12890-015-0145-5
|View full text |Cite
|
Sign up to set email alerts
|

The care needs of patients with idiopathic pulmonary fibrosis and their carers (CaNoPy): results of a qualitative study

Abstract: BackgroundIdiopathic pulmonary fibrosis (IPF) is a chronic, fibrotic interstitial lung disease of unknown origin. It has a median survival of three years but a wide range in survival rate which is difficult to predict at the time of diagnosis. Specialist guidance promotes a patient centred approach emphasising regular assessment, information giving and supportive care coordinated by a multidisciplinary team (MDT). However understanding of patient and carer experience across the disease trajectory is limited an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
159
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(161 citation statements)
references
References 23 publications
0
159
0
2
Order By: Relevance
“…Therefore, they continued to seek specific information about treatment options, symptom management and care at the end-of-life. 27 …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, they continued to seek specific information about treatment options, symptom management and care at the end-of-life. 27 …”
Section: Discussionmentioning
confidence: 99%
“…The lung tissue changes irreversibly, which results in symptoms such as dyspnoea and dry cough, which again affect patients’ everyday life. It has been shown that patients have a clear understanding of their prognosis but lack assistance with understanding how their disease will progress [35]. Exploring the patients’ perspective, Overgaard and colleagues found that the fatality of the disease was overwhelming for patients and, therefore, the dose and timing of information are tricky [36].…”
Section: Discussionmentioning
confidence: 99%
“…Exploring the patients’ perspective, Overgaard and colleagues found that the fatality of the disease was overwhelming for patients and, therefore, the dose and timing of information are tricky [36]. Sampson and colleagues showed that the patients’ initial relief associated with not being diagnosed with cancer was replaced by shock associated with the prognosis of IPF [35]. Clinical encounters, timely identification of changes in health status and functional activity and understanding of symptoms influence patients’ experiences of care.…”
Section: Discussionmentioning
confidence: 99%
“…In assenza di un supporto psicologico e sociale adeguato, le conseguenze si manifestano con un ulteriore peggioramento della qualità di vita, passando attraverso la sfiducia e quindi provocando una ridotta aderenza alle terapie e, successivamente, causando un incremento al ricorso a ricoveri ospedalieri ed accessi al pronto soccorso [73,74]. Si rende pertanto auspicabile e necessaria una migliore comprensione delle aspettative e delle esperienze dei pazienti con IPF e dei loro caregiver, poiché potrebbe contribuire a migliorare la gestione complessiva della malattia, la qualità di vita dei malati, l'aderenza e l'efficacia delle terapie.…”
Section: Impatto Economico Della Ipfunclassified